Estimation of Suitable Grade Value for Stopping Sight Distance Computation on Vertical Curves - H. Farhan, Ahmed (Iraqi Journal of Civil Engineering, 2008)
Abstract The purpose of highway geometric design is to provide safe and economical highways. One of the utmost important geometric design element for safely travel that should be satisfied is visibility on designed road. This can achieved by providing adequate sight distance in both horizontal and vertical alignments. Minimum sight distance that should be provided at all points along highway is stopping sight distance SSD. In the design of vertical curves AASHTO's Geometric design Policy uses the sight distance requirement as a major criterion in curve length determination. Moreover, sight distance has great effect on highway constructional cost because more required sight distance means more vertical curve length, which in turn means more earthwork materials. Consequently, safety and economics can be considered as a major criterion in design of highways. The AASHTO's model involved design speed, perception-reaction time, and frication factor as a parameters used for SSD computations on level sections. On inclined surfaces, an additional parameter denoted by (G), which reflect grade of sloped surface on SSD. In the present paper a new approximate methodology and Equations are formulated though which a suitable design grade value can be estimated on vertical curves where the grade not constant then utilizing this value to compute SSD on these curves and hence compute vertical curve length corrected for grade effect. Generalization of present methodology is carried out by derivation a general mathematical solution. From these derivations it has been found that the suitable grade value for Type I and Type III (initial and final grade are descending and ascending) is half of the largest grade among G1 and G2. While the design grade value is the average value of G1 and G2 for Type II and Type IV (both grade are descending or ascending). Comparison with other grade estimation on vertical curves suggestions showed that the present methodology produces more reasonable and economical value because the obtained length is no longer to be uneconomical as compared with other suggestions. At the same time it provides a safe value used in all design cases those reflects the actual case as compared with other suggestions those ignored or reduced the effect of grade.